Experiences of access to justice for persons deprived of liberty in Ecuador - Ramírez, Andrés; Machado Arévalo, Antonia (The Age of Human Rights Journal, 2021)
The Ecuadorian prison system has conditions that denotes a questionable validity of rights for inmates. In this context, access to justice (ATJ) is one of the most important rights to guarantee the rehabilitation of persons deprived of liberty (PDL) since confinement and the reality of the prison generate unique barriers for the ATJ. Through the analysis of in-depth semi-structured interviews, the ATJ experiences of the PDL and of actors linked to the social rehabilitation system are identified to state critical points in relation to the validity of this key right.